2012
DOI: 10.1177/0145445512468754
|View full text |Cite
|
Sign up to set email alerts
|

Detecting False Positives in A-B Designs

Abstract: This study evaluated the probability of generating false positives with A-B graphs. We generated 1,000 graphs consisting of three stable A-phase data points at 25% and three random B-phase data points; 1,000 graphs consisting of three stable A-phase data points at 50% and three random B-phase data points; and 1,000 graphs consisting of three random A-phase data points and three random B-phase data points. Results indicate that false positives were produced for (a) a relatively high percentage of graphs contain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…Second, we did not examine the differential effects of autocorrelation and specific phase lengths on accuracy (e.g., Fisher et al, 2003;Lanovaz et al, 2017). As a next step, researchers should conduct parametric analyses of autocorrelation and phase length while also comparing the results with other structured or statistical aids for the analysis of AB or multiple baseline designs (Ferron, Joo, & Levin, 2017;Giannakakos & Lanovaz, 2019;Krueger, Rapp, Ott, Lood, & Novotny, 2013;Manolov & Vannest, 2019). A final limitation is the large amount of data, or exemplars, required to train machine-learning models.…”
Section: Discussionmentioning
confidence: 99%
“…Second, we did not examine the differential effects of autocorrelation and specific phase lengths on accuracy (e.g., Fisher et al, 2003;Lanovaz et al, 2017). As a next step, researchers should conduct parametric analyses of autocorrelation and phase length while also comparing the results with other structured or statistical aids for the analysis of AB or multiple baseline designs (Ferron, Joo, & Levin, 2017;Giannakakos & Lanovaz, 2019;Krueger, Rapp, Ott, Lood, & Novotny, 2013;Manolov & Vannest, 2019). A final limitation is the large amount of data, or exemplars, required to train machine-learning models.…”
Section: Discussionmentioning
confidence: 99%
“…The magnitude of this problem is, however, open to debate. Using Monte Carlo simulations, researchers have shown that the probability of a type 1 error is low (i.e., < 0.05) when AB data are examined via visual analysis employing structured criteria (Fisher, Kelley, & Lomas, 2003;Krueger, Rapp, Ott, Lood, & Novotny, 2013;Novotny et al, 2014). One potential limitation of using simulated data is that the error may not correctly mimic patterns observed with human participants.…”
mentioning
confidence: 99%
“…Second, our study limited its analysis to the dual-criteria method and visual inspection. In the future, researchers may also explore other methods of data analyses to examine whether the results remain consistent (e.g., Krueger et al, 2013, Manolov & Vannest, 2020. Third, our analyses only involved simulated data as it is impossible to measure power on nonsimulated data without delving into circular reasoning.…”
Section: Discussionmentioning
confidence: 99%